2004
DOI: 10.1161/01.res.0000117583.66950.43
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mitochondrial K + Channels and Their Role in Cardioprotection

Abstract: Abstract-Twenty years after the discovery of sarcolemmal ATP-sensitive K ϩ channels and 12 years after the discovery of mitochondrial K ATP (mitoK ATP ) channels, progress has been remarkable, but many questions remain. In the case of the former, detailed structural information is available, and it is well accepted that the channel couples bioenergetics to cellular electrical excitability; however, in the heart, a clear physiological or pathophysiological role has yet to be defined. For mitoK ATP , structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
307
3
24

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(343 citation statements)
references
References 155 publications
9
307
3
24
Order By: Relevance
“…In this context, we have employed a variety of methods to identify and characterize which ion channels may be present in isolated mitochondria and in intact cells. K + channel opener compounds, including diazoxide, nicorandil and others, can protect heart cells from ischaemic or oxidative stress through a mechanism which we believe involves the opening of specific mitoK ATP channels on the inner membrane (O'Rourke 2004). Similarly, studies revealed a second class of K + channel on the mitochondrial inner membrane (mitoK Ca ), resembling the Ca 2+ -activated K + channel of the plasmalemma of certain cell types.…”
Section: Mitochondrial Ion Channels Involved In Cell Stress Responsesmentioning
confidence: 85%
“…In this context, we have employed a variety of methods to identify and characterize which ion channels may be present in isolated mitochondria and in intact cells. K + channel opener compounds, including diazoxide, nicorandil and others, can protect heart cells from ischaemic or oxidative stress through a mechanism which we believe involves the opening of specific mitoK ATP channels on the inner membrane (O'Rourke 2004). Similarly, studies revealed a second class of K + channel on the mitochondrial inner membrane (mitoK Ca ), resembling the Ca 2+ -activated K + channel of the plasmalemma of certain cell types.…”
Section: Mitochondrial Ion Channels Involved In Cell Stress Responsesmentioning
confidence: 85%
“…Their selectivity for K Ca , but not K ATP , was supported by the fact that the effects of NS1619 are not affected by the mitochondrial channel blocker 5-HD (O'Rourke, 2004;Cao et al, 2005;Sato et al, 2005) and that Pax fails to inhibit the effects of diazoxide, a K ATP channel opener (Cao et al, 2005;Sato et al, 2005). However, precautions should be taken that these two agents may have nonselective actions.…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondria are one of these important convergence points, due to their critical function in cell survival and death; notably, ATP production and apoptosis [10,12,48]. Key mitochondrial proteins, such as several potassium (K + ) channels [49][50][51][52][53] and the mitochondrial permeability transition pore (mPTP) [48,[54][55][56], act as effectors integrating these upstream signals into cardioprotective responses. The mechanisms by which CYP metabolites alter these important effectors are not well defined and require further experimentation.…”
Section: Ischemic Injury and Cardioprotectionmentioning
confidence: 99%
“…Importantly, pharmacologic data indicate that selective activation of mito K ATP confers cardioprotection following ischemia and that this channel is the major one mediating ischemic PC [59,60,63,64]. While the precise pathways by which mito K ATP activation confers cardioprotection remain unknown, potentially beneficial consequences of opening mito K ATP include partial depolarization of the intramitochondrial membrane, transient swelling of the intramitochondrial space, enhanced respiration via the electron transport chain, reduced mitochondrial calcium overload, and altered production of reactive oxygen species [59,60,64]. Cardioprotective effects of CYP2J2 overexpression involve activation of mito K ATP channels [31].…”
Section: K + Channels and Cardioprotectionmentioning
confidence: 99%